Gastric Inflammatory Fibroid Polyp: A Rare Cause of Occult Upper Gastrointestinal Bleeding - Faisal Inayat MBBS; Asad Ur Rahman MD; Ahsan Wahab MD; Amir Riaz MD; Effa Zahid MBBS; Pablo Bejarano MD; Ronnie Pimentel MD (SAGE Publishing, 2020)
Inflammatory fibroid polyps (IFPs) are rare mesenchymal lesions that can arise throughout the gastrointestinal tract. These tumors represent less than 0.1% of all gastric polypoid lesions and are frequently found incidentally on endoscopic evaluation. While presenting symptoms depend on the location of the tumor, gastric polyps commonly present with epigastric pain and early satiety. We hereby delineate the case of a middle-aged female who presented with chronic iron deficiency anemia and a positive fecal occult blood test. She underwent an upper endoscopy, which revealed an actively oozing umbilicated lesion in the gastric antrum. Endoscopic ultrasound divulged the submucosal origin of the lesion. It was subsequently excised using endoscopic mucosal resection. Pathologic examination of the resected specimen confirmed the diagnosis of gastric IFP. Furthermore, we conducted a systematic literature search of the MEDLINE database centered on gastric IFPs from January 2000 till March 2020. The data on patient demographics, clinical features, endoscopic findings, lesion site and size, and treatment approaches were collected and analyzed. This article illustrates the overarching need for clinicians to be vigilant of gastric IFPs presenting with initial clinical symptoms suggestive of occult upper gastrointestinal bleeding. Prompt diagnosis and management of gastric IFPs carry paramount importance to combat chronic unexplained iron deficiency anemia following occult bleeding in such patients. A concoction of endoscopy, biopsy, and immunohistochemical examination can be employed toward their prompt detection. Although gastric IFPs have conventionally been treated with surgery, endoscopic resection is now emerging as a safe and efficient therapeutic modality.